International experiences and domestic opportunities of applying unconventional monetary policy tools - Judit Krekó; Csaba Balogh; Kristóf Lehmann; Róbert Mátrai; György Pulai; Balázs Vonnák (Magyar Nemzeti Bank, 2013)
This paper provides an overview of the impact of unconventional central bank instruments, the relevant international experiences and the room for application in Hungary. The use of unconventional instruments may be justified by the existence of financial market friction, turmoil, failure or constraint, when instruments that change the size and/or composition of central bank balance sheets may be more efficient in achieving monetary policy objectives than traditional interest rate policy. Empirical analyses found the unconventional instruments applied in developed countries successful in easing market tensions, increasing market liquidity and reducing yields. Although they proved to be unsuccessful in providing a boost to economic growth, they were able to mitigate the fall in lending and output. Vulnerable emerging countries with a lower credit rating and high external debt have much less room for manoeuvre to apply non-conventional instruments. Even liquidity providing instruments, which are otherwise considered the least risky, may result in exchange rate depreciation and flight of capital during a crisis. The interventions that involve risk taking by the government may add to market concerns about fiscal sustainability. Due to Hungary's vulnerability, high country risk premium and large foreign exchange exposure, most of the instruments applied in other countries would entail financial stability risks at home. In theory, the sharp reduction in the supply of bank credit could provide sound justification for the use of unconventional central bank instruments in Hungary. It should be noted, however, that insufficient credit supply is mainly attributable to a lack of willingness by banks to lend, which can be less influenced by the Bank, rather than to any lack of capacity to lend. In addition to banks' high risk aversion, uncertain macroeconomic environment and economic policy measures affecting the banking sector also decreased willingness to lend, which is beyond the authority of the central bank. Therefore, these instruments at most may have a role in preventing a possible future deterioration in banks' lending capacity from becoming an obstacle to lending in a turbulent period.
Keywords: E44; E52; E58; E61; 330; monetary policy; unconventional tools; financial intermediation